The Role of Amino Acids in the Crosstalk Between Mesenchymal Stromal Cells and Neoplastic Cells in the Hematopoietic Niche - Chiu, Martina; Taurino, Giuseppe; Bianchi, Massimiliano G.; Bussolati, Ovidio (Frontiers in Cell and Developmental Biology, 2021)
Within the bone marrow hematopoietic cells are in close connection with mesenchymal stromal cells (MSCs), which influence the behavior and differentiation of normal or malignant lymphoid and myeloid cells. Altered cell metabolism is a hallmark of cancer, and changes in nutrient pools and fluxes are important components of the bidirectional communication between MSCs and hematological cancer cells. Among nutrients, amino acids play a significant role in cancer progression and chemo-resistance. Moreover, selected types of cancer cells are extremely greedy for glutamine, and significantly deplete the extracellular pool of the amino acid. As a consequence, this influences the behavior of MSCs in terms of either cytokine/chemokine secretion or differentiation potential. Additionally, a direct nutritional interaction exists between MSCs and immune cells. In particular, selected subpopulations of lymphocytes are dependent upon selected amino acids, such as arginine and tryptophan, for full differentiation and competence. This review describes and discusses the nutritional interactions existing in the neoplastic bone marrow niche between MSCs and other cell types, with a particular emphasis on cancer cells and immune cells. These relationships are discussed in the perspective of potential novel therapeutic strategies based on the interference on amino acid metabolism or intercellular fluxes.